The State of the World's Children 1990 - Fonds des Nations Unies pour l'enfance (United Nations, 1990)
Each year, UNICEF’s flagship publication, The State of the Worlds Children, closely examines a key issue affecting children. The report includes supporting data and statistics and is available in English, French and Spanish language versions.